Fatores críticos de sucesso e estágios da maturidade da gestão do conhecimento: um estudo na Embrapa - Escrivão, Giovana (2015)
The purpose of this dissertation is to relate the critical success factors to the stages of the knowledge management maturity through a empirical study. Some knowledge management maturity model were developed over the past decade, but they are incomplete, does not perform a systematic conceptual identification of the factors that should compose the model and, in most cases have a lack of empirical evidences. Consequently, there are gaps to be filled in order to develop a more complete model. Through systematic review of the literature, the critical success factors of knowledge management maturity models were compared to the critical success factors cited by knowledge management literature. The relation between these factors and the knowledge management stages were tested by empirical research. The collect data instrument was developed with assistance of knowledge management and statistics expertise’s. The Embrapa – Brazilian Enterprise for Agricultural Research was the object of this study. Embrapa is a public institution that has the aim of develops technologies, knowledge and technique and scientific information about Brazilian agriculture and livestock. The selection of the organization was guided by importance of the institution as national reference on innovation and development of new products and technology, issues deeply related to knowledge management. The data collection involved all leadership and management positions of all Decentralized Units from Embrapa, representing a population of 180 respondents from 46 organizations, with a return rate of 67,7%. The data was analyzed through descriptive statistics, linear regression techniques, Fisher’s exact test and polytomous logistic regression. As main result, among others, we could characterize the critical success factors in knowledge management stages and identify associations between these variables (critical success factors and knowledge management stages), showing, for example, that the technology and the top management support have an important role, mainly, at the second stage.